Climate change impacts on coastal ecosystems - Ryan Guild; Xiuquan Wang; Pedro A Quijón (Environmental Research: Climate)
As the planet undergoes unprecedented climate changes, coastal ecosystems stand at the frontline of ocean-land interactions and environmental changes. This overview explores the various climate-related challenges transforming coastal ecosystems and their responses to these pressures. Key climate-related stressors—including warming, sea level rise, ocean acidification, changes to freshwater availability, and shifts in circulation and disturbance patterns—pose significant threats to both the structure and function of these ecosystems. These stressors impact every level of biological organization, with modern responses manifesting as ecosystem degradation and shifts toward simpler, less biodiverse states—trends likely to intensify with ongoing emissions. Compounded by local human disturbances, these stressors risk overwhelming the adaptive capacity of coastal ecosystems, restructuring coastal food webs, and compromising the essential ecosystem services that currently underpin productivity, storm protection, and water quality in coastal zones. Future trajectories of change in coastal ecosystems will largely depend on the extent of future greenhouse gas emissions and human activities in and around coastal zones. However, critical knowledge gaps remain, particularly regarding the interactions among stressors and the nature of ecological tipping points. Addressing these gaps through further research will be necessary to improve projections of future impacts and support the conservation and resilience of these valuable ecosystems.